Transcription Factor SOX5 Promotes the Migration and Invasion of Fibroblast-Like Synoviocytes in Part by Regulating MMP-9 Expression in Collagen-Induced Arthritis - Shi, Yumeng; Wu, Qin; Xuan, Wenhua; Feng, Xiaoke; Wang, Fang; Tsao, Betty P.; Zhang, Miaojia; Tan, Wenfeng (Frontiers in Immunology, 2018)
Objectives. Fibroblast-like synoviocytes (FLS) exhibit a unique aggressive phenotype in rheumatoid arthritis (RA). Increased FLS migration and subsequent invasion of the extracellular matrix are essential to joint destruction in RA. Our previous research reported that transcription factor SOX5 was highly expressed in RA-FLS. Here, the effects of SOX5 in RA-FLS migration and invasion will be investigated. Methods. The migration and invasion of RA-FLS were evaluated using a transwell chamber assay. The expression of several potential SOX5-targeted genes, including matrix metalloproteinases (MMP-1, 2, 3 and 9), chemokines (CCL4, CCL2, CCR5 and CCR2) and proinflammatory cytokines (TNF- and IL-6) were examined in RA-FLS using SOX5 gain-and loss-of-function study. The molecular mechanisms of SOX5-mediated MMP-9 expressions were assayed by luciferase reporter gene and ChIP studies. The in vivo effect of SOX5 on FLS migration and invasion was examined using collagen-induced arthritis (CIA) in DBA/1J mice. Results. Knockdown SOX5 decreased lamellipodium formation, migration and invasion of RA-FLS. The expression of MMP-9 was the only gene tested and concomitantly affected by silencing or overexpressing SOX5. ChIP assay revealed that SOX5 was bound to the MMP-9 promoter in RA-FLS. The overexpression of SOX5 markedly enhanced the MMP-9 promoter activity, and specific deletion of a putative SOX5 binding site in MMP-9 promoter diminished this promoter-driven transcription in FLS. Locally knocked down SOX5 inhibited MMP-9 expression in the joint tissue and reduced pannus migration and invasion into the cartilage in CIA mice. Conclusions. SOX5 plays a novel role in mediating migration and invasion of FLS in part by regulating MMP-9 expression in RA.